Management of Neck Injury with Tracheal Perforation Due to Rubber Band in Monkey: A Case Report - Jain, Reshma; Shukla, B. P.; Chaurasia, Astha; Shukla, Nishant (Chronicle of Bioresource Management, 2021)
The article presents penetrating trauma of neck in monkey wound all around the neck since 10 days and its management. The injury was deep in the ventral part of neck with perforation of trachea as air was coming out during the respiration. Surgical management was planned under the general anaesthesia using xylazine and ketamine. During cleaning an embedded rubber band was observed in the wound encircled all around the neck. Injured tissue was closed by putting opposition sutures using Mesrsilk no.0 leaving the counter opening. Care taker was advised for daily dressing for 4 days than alternate dressing until complete healing. Parental antibiotic Inj. Cefotaxim for 07 days and analgesic Sy. Meloxicam for 3 days were recommended post operatively. On 20th post-operative day skin wound was completely healed except a tiny opening on ventral aspect. The prognosis for tracheal rupture cases is excellent when diagnosed and treated appropriately.